2016
DOI: 10.1080/14773996.2016.1256553
|View full text |Cite
|
Sign up to set email alerts
|

Occupational safety in a globalized construction industry: a study on Polish workers in Norway*

Abstract: Polish workers are the largest group of migrant workers in Norway and are particularly well represented in the construction industry. According to several studies, migrant workers are more prone to occupational accidents than native workers are. This difference is often attributed to poor communication and lack of linguistic skills. We explored factors affecting occupational safety related to migrant workers with an emphasis on communication, culture and language through interviews with Polish and Norwegian wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(24 reference statements)
2
9
0
Order By: Relevance
“…The kind of reasons for having accidents raised by participants are consistent with the results of earlier studies [5, 30]. Associations between working conditions (i.e., long working hours, language problems, lack of safety training) and health problems including accidents at work are well documented in migrants working in unskilled jobs [11, 15, 17, 24, 36, 37].…”
Section: Discussionsupporting
confidence: 87%
“…The kind of reasons for having accidents raised by participants are consistent with the results of earlier studies [5, 30]. Associations between working conditions (i.e., long working hours, language problems, lack of safety training) and health problems including accidents at work are well documented in migrants working in unskilled jobs [11, 15, 17, 24, 36, 37].…”
Section: Discussionsupporting
confidence: 87%
“…One reason the workers gave was that they do not wish to report on others to the management. These findings also coincide with previous research (Wasilkiewicz et al, 2016). However, these major differences were not found for all aspects related to safety.…”
Section: Differences Between Migrant and Norwegian Workerssupporting
confidence: 94%
“…A study of Polish construction workers in Norway found that the construction culture in Poland differed from the construction culture in Norway and these differences, as much if not more than language differences, acted as determinants of the workers' OHS experiences and practices. 63 For instance, worker voice was expressed differently in Polish construction firms: for Polish workers in Norway, speaking up or filing incident reports was seen as "snitching," while this was not the case for Norwegian workers. Even without shared language, however, a skilled foreign worker could be acknowledged and respected by Norwegians in the same trade because of the shared skill set.…”
Section: Determinants Of Supportive and Detrimental Ohs Practicesmentioning
confidence: 99%